Cultivating spiritual awareness in Islamic primary education through contemplative pedagogy: a quasi-experimental study - Sa’idatus Sariroh; Iwan Kuswandi; Framz Hardiansyah (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
This study investigates the effectiveness of contemplative pedagogy in cultivating spiritual awareness among students in Islamic primary education. Addressing the limited empirical evidence on pedagogical approaches that foster students’ inner spiritual development, this study employed a quasi-experimental design using a non-equivalent control group pretest–posttest model. The participants were 80 Grade 5 students from an Islamic primary school in Sumenep Regency, Indonesia, divided into an experimental group (n = 40) and a control group (n = 40). Spiritual awareness was measured using a validated questionnaire administered before and after the instructional intervention. Descriptive analysis showed that both groups had comparable pretest scores (experimental M = 67.85; control M = 68.10). After the intervention, the experimental group demonstrated a substantially higher posttest mean score (M = 82.40) compared to the control group (M = 73.25). The mean gain score of the experimental group (ΔM = 14.55) exceeded that of the control group (ΔM = 5.15). Inferential analysis using analysis of covariance (ANCOVA) revealed a significant effect of contemplative pedagogy on students’ spiritual awareness after controlling for pretest scores, F(1, 77) = 48.47, p < .001, with a large effect size (partial η² = .386). These findings provide empirical evidence that contemplative pedagogy is a practical instructional approach for enhancing students’ spiritual awareness—particularly in terms of God-conscious awareness, reflective meaning-making of Islamic values, moral self-regulation, and commitment to value-based action—in Islamic primary education.